Caffeine use in a Super Rugby game and its relationship to post-game sleep - Dunican, I.; Higgins, C.; Jones, M.; Clarke, M.; Murray, K.; Dawson, B.; Caldwell, J.; Halson, S.; Eastwood, Peter (Taylor and Francis Group, 2018)
© 2018 European College of Sport Science Objective: To examine the relationship between regular game-related caffeine consumption on sleep after an evening Super Rugby game. Methods: Twenty elite rugby union players wore a wrist-activity monitor to measure sleep for three days before, three days after and on the night of an evening Super Rugby game (19:00–21:00). Players ingested caffeine as they would normally (i.e. before and sometimes during a game) and saliva samples were collected before (17:00) and after (21:30) the game for caffeine concentration. Results: Compared to the nights leading up to the game, on the night of the game, players went to bed 3 h later (23:08?±?66 min vs 02:11?±?114 min; p? < ?.001) and had 1:30 hh:mm less sleep (5:54?±?2:59 vs 8:02?±?1:24 hh:mm; p? < ?.05) and four players did not sleep after the game. Post-game caffeine saliva concentrations were greater than pre-game levels in 17 players (Pre-game 0.40 µg/mL vs Post-game 2.77 µg/mL; p? < ?.001). The increase in caffeine saliva concentrations was moderately associated with an increase in sleep latency (p? < ?.05), a decrease in sleep efficiency (p? < ?.05), and a trend for a decrease in sleep duration (p?=?.06) on game night. Conclusion: Caffeine consumption before a Super Rugby game markedly increases post-game saliva caffeine levels. This may contribute to the observed 3.5 h delay in time at sleep onset and the 1.5 h reduction in sleep duration on the night of the game. This study highlights the need for a strategic approach to the use of caffeine within a Super Rugby team considering the potential effect on post-game sleep.